Malay Etnomathematic of Riau and Riau Islands: Systematic Literature Review - Deswita, Hera; Muslim, Suyitno (Jurnal Pendidikan MIPA, 2021)
Ethnomathematics can be used as an approach to mathematics learning in both primary and secondary schools. The study of ethnomathematics is gaining popularity, but few studies still discuss ethnomathematics extracted from the culture of the people in Riau and Riau Islands. They have cultural similarities, namely Riau Malay. The purpose of this study is to describe and provide an overview of the Riau Malay ethnomathematical studies that have been studied from the Riau Malay lands. The method used in this study is Systematic Literature Review (SLR). This study discusses 13 articles published between 2016-2021. The research results show that ethnomathematical studies have not been spread throughout the Riau and Riau Islands regions. The form of culture revealed in this study is still dominated by community activities. Ethnomathematical studies are still dominantly related to the concept of geometry, which means that most of the activities found are Designing. The limitations of some of these studies can serve as further studies for other researchers to explore the ethnomathematics of elements of Riau Malay culture and other Riau Islands.Keywords: ethnomathematics, Riau Malay and Riau Islands, systematic literature. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp216-225